MicroRNA-21, -126 and -146a as potential novel systemic markers of metabolic syndrome - Tuominen, Jenni (2018)
Obesity and overweight have reached epidemic proportions. These conditions increase the risk of numerous health problem, including metabolic syndrome (MetS). Hormonal changes during menopause transition may be related to the increased frequency of the MetS. Circulating microRNAs (miRNAs) are easily detectable in blood and have a potential to act as non-invasive biomarkers. MiR-21, miR-126, and miR-146a were selected in this Master’s thesis because they are associated with MetS risk factors and menopause-related hormone estradiol (E2). Hypothesis of this study was that circulating miR-21, miR-126 and miR-146a levels may vary in different MetS risk factor groups and stage of menopause. Participants (n=137) were divided to the MetS risk factor groups; healthy (n=35), risk 1 (n=35), risk 2 (n=33), and MetS (n=34), based on anthropometrics and measured blood characteristics. Menopause groups; pre- (n=45), peri- (n=44) and postmenopause (n=48) were divided based on blood test and menstrual diary. Circulating miRNAs levels were quantified with quantitative polymerase chain reaction (qPCR). The results could not establish distinct association between serum miR-21, miR-126 and miR-146a to the risk factor groups of MetS or to the stage of menopause. However, significant correlation was observed between miR-21 and E2, miR-21 and glucose and miR-126 and glucose. Based on the results of this thesis, despite the associations found between miRNAs and glucose, the studied miRNAs cannot be considered as markers of MetS.